The Use of Ammonium Sulphate for Partial Purification of Proteases Obtained from the Latex of Milkweed Plant (Calotropis gigantea) - Witono, Yuli; Subagio, Achmad; Widjanarko, Simon Bambang; Aulanni'am, Aulanni'am (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The latex of milkweed plant (Calotropis gigantea) is known to have proteolytic activities. The research was conducted to evaluate the use of ammonium sulphate for partial purification of such enzymes. The phosphate buffer extract of the latex was first centrifuged to precipitate gum and non-proteinous matter. The supernatant was then treated with ammonium sulphate to achieve the respective degree of saturation, namely 35, 50, 65 and 80%. It showed that the use of ammonium sulphate at 65% degree of saturation was the optimum condition, and produced a partially purified enzyme with proteolytic activity which was not significantly different from that obtained from the use of the same salt at 80% degree of saturation. Nonetheless, the supernatant still showed a substantial degree of proteolytic activity, indicating that the latex contained a various types of proteases. Key Word: Milkweed plant (Calotropis gigantea), protease, partial purification